2011
DOI: 10.1007/s00421-011-2283-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood lactate concentration at the maximal lactate steady state is not dependent on endurance capacity in healthy recreationally trained individuals

Abstract: The aim of the study was to investigate the independent relationship between maximal lactate steady state (MLSS), blood lactate concentration [La] and exercise performance as reported frequently. Sixty-two subjects with a wide range of endurance performance (MLSS power output 199 ± 55 W; range: 100-302 W) were tested on an electronically braked cycle ergometer. One-min incremental exercise tests were conducted to determine maximal variables as well as the respiratory compensation point (RCP) and the second lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
1
13
1
Order By: Relevance
“…Lucia and co-workers [ 4 ] detected a high agreement between VT 1 and LT (321±8 W vs. 319±10 W) in elite endurance cyclists, and our data corroborates their findings in well trained cyclist. On the other hand, in an attempt to locate the VT 2 workload through a CBL test, Smekal et al [ 36 ] found that a value of 4.1±1.0 mMol·L -1 agrees with VT 2 in active and healthy men and women, which coincides with our findings ( Table 1 ). Nevertheless, Davis and co-workers [ 37 ] suggest that anaerobic thresholds have frequently been determined using blood lactate concentrations of less than 2 mMol·L -1 as a reference point.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lucia and co-workers [ 4 ] detected a high agreement between VT 1 and LT (321±8 W vs. 319±10 W) in elite endurance cyclists, and our data corroborates their findings in well trained cyclist. On the other hand, in an attempt to locate the VT 2 workload through a CBL test, Smekal et al [ 36 ] found that a value of 4.1±1.0 mMol·L -1 agrees with VT 2 in active and healthy men and women, which coincides with our findings ( Table 1 ). Nevertheless, Davis and co-workers [ 37 ] suggest that anaerobic thresholds have frequently been determined using blood lactate concentrations of less than 2 mMol·L -1 as a reference point.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with Skinner and McLellan [ 41 ], our results showed that MLSS does not correspond to VT 1 (aerobic threshold) or VT 2 (anaerobic threshold) but represents an intermediate intensity between both physiological events. This finding is important since numerous authors have proposed that the workload at VT 2 coincides with the one for MLSS [ 36 , 42 ], making it difficult for coaches and sport scientists to effectively communicate their findings and the effects produced by different training intensities. Other authors have tried to estimate the MLSS workload through CBL detected during a GXT.…”
Section: Discussionmentioning
confidence: 99%
“…The MLSS constitutes another essential physiological event in endurance performance, as it is the maximal workload that can be maintained without elevations in blood lactate concentration (MLSS). Previous authors have proposed that MLSS workload coincides with the one for VT 2 (Smekal et al, 2012 ). In contrast to this assumption, recent investigations in cyclists elucidated that MLSS may correspond to a lower exercise intensity of VT 2 and matches better with the midpoint between both ventilatory thresholds (Pallarés et al, 2016 ; Peinado et al, 2016 ).…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies in experimental model and clinical studies have shown that lactate concentration in the steady state is independent of resistance capacity [13][14][15] . In humans, particularly, Beneke, Hütler, Leithäuser 11 verified that MLSS as well as MLSS intensity are independent of performance, however, subjects with higher performance have higher MLSS workloads.…”
Section: Introductionmentioning
confidence: 99%